Problems Of Studying the Everyday Life Of The Urban Population Of Karakalpakstan In The 1960s–1980s - Seydametova Gulnara Utarbaevna; Davletiyarov Madatbay Maxsetbayevich (International Journal Of History And Political Sciences, 2025)
The author in referenced article had attempted to analyze the ways of formation the history of everyday life in world historiography to include fact that in France in the middle of XX century by efforts of representatives of the school of annals this area of history gained status of independent direction. In addition to this in article are considered the issues related to the development of this area of history in Germany and some other countries. Besides was conducted analysis of researches related to the history of everyday life in Russia at the End of XX – Beginning of XXI centuries. It Is notes that the study to everyday urban life in the economic, social and cultural conditions of Karakalpakstan mid-1960s, mid-1980s, will provide an opportunity to study the processes of formation of the social infrastructure of cities of Karakalpakstan